Cluster and principal component analyses for assessment of genetic diversity in Saccharum spontaneum - V, Vinu; T, Lakshmi Pathy; Pazhany, Adhini S; S, Karthigeyan (Journal of Sugarcane Research, 2023)
Forty three Saccharum spontaneum accessions were evaluated using eighteen drought tolerance related traits. The Euclidean based dendrogram divided the accessions into three different clusters. Euclidean distances ranged from 7.65 to 140.23. The maximum distance was reported between the accessions IND 99-849 and IND03- 1247. From the PCA analysis, it is observed that 47.03% of the total variation was accounted by the ﬁrst two principal components. The variables factor map visualized that stalk height at 90 days and stalk height during stress were the two important variables contributing maximum to the total variation. In the case of Euclidean distance based clustering cluster I included drought tolerant accessions while it was cluster II and III for PCA based clustering accessions viz., IND 99-847, IND 08-1500, IND 08-1491, IND 99-984, IND 02-1186 etc. were identiﬁed as promising under drought condition. These accessions can be utilized in the sugarcane improvement programmes for abiotic stress tolerance. The understanding of genetic diversity present in germplasm is important for their proper utilization, management and conservation.